Posisi Atas Maupun Bawah Yang Penting Happy: Relaksasi Terhadap Sifat Qana’ah - Ngatoillah Linnaja; Robingun Suyud El Syam (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
Human life is like a cart wheel where the cycle of fate will always run along the path determined by God. It is necessary to respond to the phenomenon of uncertainty in fate so that one does not fall into despair. So, the aim of this article is to try to explore the important up and down positions of happiness: relaxation of the nature of qana'ah, as a solution to the uncertain cycle of life. Through a phenomenological approach, the research results show that the qonaah attitude is able to answer the probalematics of uncertainty in human fate. The Qanaah attitude is an application of an attitude of gratitude, which has proven to be effective as self-therapy for psychological illnesses which often have a negative impact on physical health. The Qonaah attitude is an application of gratitude which has been proven to be effective as self-therapy for psychological illnesses which often have a negative impact on physical health. This is because within a person there will be an attitude of acceptance of reality, whether he is sick or healthy, when he is well off, poor or deficient. The implication of the research is that the nature of qonaah is needed as a habit so that it becomes a character. Research is expected to contribute to the development of Islamic education.